Efisiensi, Restrukturisasi, dan PHK Massal: Batas Perlindungan Hukum Bagi Pekerja dalam Strategi Bisnis Korporasi - Indra Wijaya; Arrum Budi Leksono (LPPM Iblam School of Law, 2026)
Efficiency and restructuring have become primary corporate strategies in responding to the pressures of globalization, technological disruption, and economic uncertainty. In practice, these strategies are often realized through mass layoffs, which have significant social, economic, and psychological impacts on workers. This article aims to analyze the position of mass layoffs within the framework of business law, examine the extent to which labor law provides substantive and procedural protection for workers, and define the limits of legal legitimacy for corporations' use of efficiency as an excuse without neglecting the principles of justice and worker protection.This research uses a normative legal research method with a statutory and conceptual approach, accompanied by a limited comparative approach through a review of national and international empirical literature. The analysis is conducted qualitatively using prescriptive reasoning regarding labor law norms, the doctrine of business judgment, and the principles of worker protection in industrial relations. The results indicate that efficiency and restructuring can legally serve as grounds for mass layoffs as long as they meet the limits of legal legitimacy, namely, proving the rationality of the efficiency rationale, adherence to the principles of good faith and proportionality, fulfilling due process, and fulfilling workers' normative rights. Mass layoffs conducted without meeting these parameters have the potential to exceed legitimate business discretion and violate the principle of worker protection. This article emphasizes the importance of corporate accountability and strengthened legal oversight mechanisms to ensure that business efficiency is not pursued at the expense of social justice in industrial relations.